The benefits of educational tales in teacher and student perspective - Muhammad Nur Wangid (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
This study aims to analyze teacher and student perspectives on educational fairy tales as instructional learning materials. The research was involved 20 teachers and 400 students of forth grade of elementary school in Yogyakarta Province. The data collection techniques used were questionnaires and interviews. Researcher used descriptive statistical data analysis techniques. This technique was used to describe the perception of teachers and students about the benefits of educational tales in percentage calculation. The results show that teachers and students have a high positive perspective on the presence of educational fairy tales as learning support teaching materials. It was known the teacher perspective a percentage of 91.50% and 98.00% students in terms of attractiveness of educational fairy tales. While on the aspect of the utilization of educational fairytale books as teaching materials, teachers and students provide a percentage of 92.50% and 93.00%. In its usefulness for build character value, the teacher gives the percentage of 97,75% and the student equal to 86.00% with the category of very good, then on the utilization aspect of educational fairy tale to the development of cognitive ability of the child, the teacher gives the percentage of 92.00% and for the student is 88.75% that mean very good category. This means that teachers and students, both have a high perspective that a fairy tale containing educational elements can generate a sense of interest, usefulness in learning, can be a medium of character values in children and can stimulate the development of cognitive abilities of children.